2014
DOI: 10.1007/s12032-014-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of novel lncRNA RP11-462C24.1 suggests a biomarker of poor prognosis in colorectal cancer

Abstract: Long noncoding RNAs (lncRNAs) have recently emerged as a major class of regulatory molecules, which were involved in a broad range of biological processes and complex diseases. Research on lncRNAs may shed light on tumorigenesis and progression of colorectal cancer (CRC). The purpose of the present study was to identify lncRNAs correlated with CRC and then investigate their potential functions. We selected 92 patients for this prospective study and then collected the tumor samples and clinical records. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 40 publications
2
60
1
Order By: Relevance
“…LncRNA-H19 can increase cell invasion and metastasis in bladder cancer through associating with EZH2 and inhibiting E-cadherin (19), while LncRNA-EBIC is found to promote tumor invasion by similar mechanism in cervical cancer (18). Aberrant expressed lncRNAs also unravelled their importance in CRC (20)(21)(22)(23)(24)(25). However, most of lncRNA studies focused on correlations of clinicopathological characteristics and prognosis, the mechanisms are rarely clarified, especially for mCRC.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA-H19 can increase cell invasion and metastasis in bladder cancer through associating with EZH2 and inhibiting E-cadherin (19), while LncRNA-EBIC is found to promote tumor invasion by similar mechanism in cervical cancer (18). Aberrant expressed lncRNAs also unravelled their importance in CRC (20)(21)(22)(23)(24)(25). However, most of lncRNA studies focused on correlations of clinicopathological characteristics and prognosis, the mechanisms are rarely clarified, especially for mCRC.…”
Section: Discussionmentioning
confidence: 99%
“…Shi and colleagues [51] selected 92 patients for a prospective analysis of association between lncRNA expression and clinical characteristics. Their results showed that the expression level of lncRNA RP11-462C24.1 was lower in CRC tissues compared with adjacent normal samples, indicating the potential roles of RP11-462C24.1 in tumorigenesis and progression of CRC.…”
Section: Other Lncrnasmentioning
confidence: 99%
“…20 However, works by us and others suggest that lncRNAs may play causative roles in gastrointestinal tumors. [32][33][34][35][36][37] We have also demonstrated the significance of lncRNAs as potential biomarkers for CRC, 38,39 as well as for the status of gut microorganisms. 40 Given the implications of lncRNAs in CRC, the effects of CNAs on lncRNAs should be further explored.…”
Section: Cnas In Crcmentioning
confidence: 99%